RNAi prevents and reverses phenotypes induced by mutant human ataxin‐1. Issue 5 (2nd November 2016) - Keiser, Megan S.; Monteys, Alejandro Mas; Corbau, Romuald; Gonzalez‐Alegre, Pedro; Davidson, Beverly L.
Abstract : Objective: Spinocerebellar ataxia type 1 is an autosomal dominant fatal neurodegenerative disease caused by a polyglutamine expansion in the coding region of ATXN1 . We showed previously that partial suppression of mutant ataxin‐1 (ATXN1) expression, using virally expressed RNAi triggers, could prevent disease symptoms in a transgenic mouse model and a knockin mouse model of the disease, using a single dose of virus. Here, we set out to test whether RNAi triggers targeting ATXN1 could not only prevent, but also reverse disease readouts when delivered after symptom onset. Methods: We administered recombinant adeno‐associated virus (rAAV) expressing miS1, an artificial miRNA targeting human ATXN1 mRNA (rAAV.miS1), to a mouse model of spinocerebellar ataxia type 1 (SCA1; B05 mice). Viruses were delivered prior to or after symptom onset at multiple doses. Control B05 mice were treated with rAAVs expressing a control artificial miRNA, or with saline. Animal behavior, molecular phenotypes, neuropathology, and magnetic resonance spectroscopy were done on all groups, and data were compared to wild‐type littermates. Results: We found that SCA1 phenotypes could be reversed by partial suppression of human mutant ATXN1 mRNA by rAAV.miS1 when delivered after symptom onset. We also identified the therapeutic range of rAAV.miS1 that could prevent or reverse disease readouts. Interpretation: SCA1 disease may be reversible by RNAi therapy, and the doses required for advancing this therapy to humans are delineated. Ann Neurol 2016;80:754–765